2016
DOI: 10.1002/bio.3073
|View full text |Cite
|
Sign up to set email alerts
|

Structure and photoluminescent properties of green‐emitting terbium‐doped GdV1−xPxO4 phosphor prepared by solution combustion method

Abstract: Terbium-doped gadolinium orthovanadate (GdVO4 :Tb(3+) ), orthophosphate monohydrate (GdPO4 ·H2 O:Tb(3+) ) and orthovanadate-phosphate (GdV,PO4 :Tb(3+) ) powder phosphors were synthesized using a solution combustion method. X-Ray diffraction analysis confirmed the formation of crystalline GdVO4 , GdPO4 ·H2 O and GdV,PO4 . Scanning electron microscopy images showed that the powder was composed of an agglomeration of particles of different shapes, ranging from spherical to oval to wire-like structures. The chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…[6] As-prepared samples after hydrothermal process at 180 o C or 200 o C are also presented hexagonal phase, [8,9] then the phase will completely transform from hexagonal to monoclinic phase when annealed at 700 o C. [8,9] While Lanchun Zou reported that, it still was hexagonal GdPO 4 .H 2 O phase when sample was canlcined at 700 o C and pure monoclinic GdPO 4 phase could acquired when the reaction temperature was up to 800 and 900 o C. [6] By combustion synthesis, broad diffraction peaks of monoclinic phase were obtained in as-prepared GdPO 4 :Ho 3+ ,Yb 3+ samples annealed at 250 o C, and sharp diffraction peaks of monoclinic phase were receilved; [10] while for the case of GdPO 4 :Tb 3+ samples, hexagonal GdPO 4 .H 2 O phase (JCPDS No. 39-0232) was observed till annealed at 600±10 o C. [11] The SEM image of GdPO 4 :Eu 3+ nanopowders annealed at 900 °C is shown in Fig. 2.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…[6] As-prepared samples after hydrothermal process at 180 o C or 200 o C are also presented hexagonal phase, [8,9] then the phase will completely transform from hexagonal to monoclinic phase when annealed at 700 o C. [8,9] While Lanchun Zou reported that, it still was hexagonal GdPO 4 .H 2 O phase when sample was canlcined at 700 o C and pure monoclinic GdPO 4 phase could acquired when the reaction temperature was up to 800 and 900 o C. [6] By combustion synthesis, broad diffraction peaks of monoclinic phase were obtained in as-prepared GdPO 4 :Ho 3+ ,Yb 3+ samples annealed at 250 o C, and sharp diffraction peaks of monoclinic phase were receilved; [10] while for the case of GdPO 4 :Tb 3+ samples, hexagonal GdPO 4 .H 2 O phase (JCPDS No. 39-0232) was observed till annealed at 600±10 o C. [11] The SEM image of GdPO 4 :Eu 3+ nanopowders annealed at 900 °C is shown in Fig. 2.…”
Section: Methodsmentioning
confidence: 94%
“…Several methods have been reported for the synthesis of rare-earth doped GdPO 4 crystals, such as co-precipitation, [5] hydrothermal, [6][7][8][9] sol-gel. [10] As far as we know, few studies have been published on synthesis of rare-earth doped GdPO 4 nanocrystals, such as GdPO 4 :Ho 3+ ,Yb 3+ [10] and GdPO 4 :Tb 3+ , [11] and no work has been reported on the synthesis of GdPO 4 :Eu 3+ nanocrystals by combustion method. We herein present a straightforward combustion method to prepare Eu 3+ doped GdPO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Luminescent rare-earth (RE) oxides have been extensively explored both in terms of theoretical detailing of 4f–4f transitions and for their unique applicability in lighting, visualization, nonlinear optics, and biolabeling technologies. RE vanadates (REVO 4 ) are chemically stable and remarkably versatile hosts for lanthanoid (Ln) optical centers with downshift and upconversion emissions, which enable emerging applications in nanothermometry, sensing, and catalysis. While Eu 3+ -doped YVO 4 is an ubiquitous UV-excited red phosphor, ,,, the inactivity of Tb 3+ -doped YVO 4 is an intriguing aspect in the chemistry and spectroscopy of vanadate-based luminescent materials. ,, During the search for efficient lamp phosphors in the late 1960s, many groups reported the complete absence of Tb 3+ luminescence in YVO 4 as well as the strong quenching of other Ln 3+ emissions induced by Tb 3+ -codoping. Even though some groups studied Tb 3+ emissions in lanthanum (LaVO 4 ) or gadolinium (GdVO 4 ) vanadates, papers mentioning any luminescence in tetragonal YVO 4 :Tb 3+ are scarce, ,,, and no spectra or detailed characterization have been reported. The description of the Tb 3+ luminescence in AXO 4 zircon-type solids has been mainly performed for yttrium phosphates (YPO 4 ), phosphovanadates (YP 1– x V x O 4 ), and arsenovanadates (YAs 1– x V x O 4 ), which are isostructural to YVO 4 . , …”
mentioning
confidence: 99%